PENGARUH DEMOGRAFI DAN LITERASI KEUANGAN TERHADAP PRAKTIK MANAJEMEN KEUANGAN PERSONAL (Studi Kasus Pada Guru Pegawai Negeri Sipil di Kabupaten Kuningan ) - Ita Novita; Herma Wiharno (Universitas Kuningan, 2022)
The objective of this study were to examine the influence of demography and financial literacy on personal financial management practice. Demographics in this study were devided into dimensions of gender, education level, age, number of dependents and salary class. While financial literacy was devided into financial Knowledge dimension, financial behavior and financial attitude. The amount of samples used were 375 teachers with Cluster Proportional Random Sampling. Logistic Regression with SPSS 19 and Minitab 16 used as technique of analysis. The analysis showed that gender, education level, age, number of dependents, salary class, financial knowledge, financial behavior, and financial attitudes together had a significant effect on personal financial management practices. Mean while, partially only the variables of age, number of dependents, salary class, financial knowledge (financial knowledge), and financial behavior have a significant effect on personal financial management practices. Meanwhile, the variables of gender, education level, and financial attitude partially have no significant effect on the personal financial management practice of PNS teachers in Kuningan Regency. The magnitude of the contribution or the influence of the variables of gender, education level, age, and salary group, financial knowledge, financial behavior, and financial attitude personal financial management practice is 42.1%, the rest the remaining 57.9% is the contribution of the variables outside the model. Keywords : gender, education level, age, numbers of dependent, salary class, financial knowledge, financial behaviour, financial attitude, personal financial management practice.